Promoted Viability and Differentiated Phenotype of Cultured Chondrocytes With Low Level Laser Irradiation Potentiate Efficacious Cells for Therapeutics - Yang, Xiaohong; Liu, Timon Chengyi; Liu, Shaojie; Zhu, Weicong; Li, Honglin; Liang, Peihong; Ye, Suihui; Cui, Shuliang (Frontiers in Bioengineering and Biotechnology, 2020)
Effective clinical treatments of cartilage lesions in defected joints essentially require great number of active chondrogenic cells by either in vivo stimulation or largely relying on ex vivo passaging in cultivation of small biopsy specimen. However, conventional passaging of cultured chondrocytes provides the number of cells for treatments but usually loses their differentiated phenotype, leading to the formation of fibrocartilaginous tissue resulted in malfunctional repairs. Here, passaged chondrocytes are treated with low level laser irradiation (LLLI) as a modulator in the culture system for producing cells potentially applicable in clinical therapies. The LLLI shows evidence of chondroprotective effects by enhanced synthetic features and promoted gene expression pattern in favor of cell growth and reducing apoptosis, particularly through attenuating IL-1β-induced upregulation of mediators/regulators of cell death cascade. The treatments yield great number of chondrocytes with higher viability compared to the untreated cells. The LLLI is also premiere in showing its ability to ameliorate and uphold differentiated phenotype of the chondrocytes simultaneously. The LLLI-treated chondrocytes in culture are promising cell source (material) for developing tissue engineering strategies for cell-based therapies of cartilage lesions aiming at the restoration of articular function.